Pear phytobezoar as a rare cause of small bowel obstruction: a case report - Yu, Kuanyong; Feng, Wenjun; Liu, Liyang; Cao, Chuanyang; Qiang, Guanghui (Frontiers in Medicine, 2025)
A phytobezoar is an accumulation of indigestible fruit and vegetable fibers in the gastrointestinal (GI) tract. Small bowel obstruction (SBO) caused by phytobezoars is infrequent, and pear-induced instances are extremely rare. We present a 45-year-old woman with a 5-day history of colicky abdomen discomfort, nausea, vomiting, abdominal distention, and no bowel movements. She had two cesarean sections but no prior GI issues and had eaten an extensive quantity of pears 2 days before symptom onset. A physical examination showed discomfort, distension, and decreased bowel sounds in the abdomen. Laboratory testing was normal, but computed tomography (CT) revealed dilated small intestine loops and a transition point in the right lower abdomen. Conservative treatment, which included fasting, intravenous fluids, antibiotics, and nasogastric decompression, failed. A 30 mm × 30 mm pear bezoar blocking the terminal ileum was removed through a 4-cm enterotomy during laparoscopy. The enterotomy was closed transversely, and the patient healed normally, remaining symptom-free 3 months later. This case emphasizes the value of staying aware of phytobezoar-induced SBO in individuals’ patients who have not previously undergone stomach surgery. Early dietary history, imaging characteristics, and timely surgical intervention are crucial. Individualized dietary counseling can aid in preventing recurrence in at-risk patients.